Does David Make A Goliath? Impact of Rival's Expertise Signals on Online User Engagement - Tandon, Ayushi (My University, 2024)
How does information on a rival’s expertise influence the focal user’s engagement in online competitive settings? Online competitive settings differ fundamentally from other online contexts, such as e-commerce and social media platforms, explored in the prior work. This contextual distinction, we argue, is important as it determines the relationship between information about others and the focal user’s engagement. The relevance of this question relates to broader theoretical ambiguities concerning the effects of status and past performance as relative and absolute signals of expertise. Our findings are based on a field experiment in which we modified the multiround mobile two-player gaming app interface, randomly exposing players to rival’s status and past performance signals. We measure the focal user’s engagement regarding their decision to continue the game after each round. As a baseline, we find that the focal user is less likely to continue the game if the rival exhibits higher current performance. However, the rival’s status and past performance signals create strong contingencies wherein the principle effect of current performance is stronger if the rival has a high status or moderate past performance. Further, these contingent effects are partly predicated on the focal player’s motivation to compete. These findings offer several important implications for driving user engagement in online competitive settings and meaningfully advance our current understanding of the effects of status and past performance information on online engagement.
PUBLISHED
Keywords: Digital Engagement; Digital Platform; user engagement